THE EFFECT OF HUMAN RESOURCE DEVELOPMENT ON EMPLOYEE PERFORMANCE AT PT. NUSANTARA PLANTATION V PEKANBARU - Zakaria; Aisyah Rahman; Suyatni (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
The purpose of this study was to determine the effect of human resource development on employee performance. This research was conducted with the title